A novel multi-functional binder based on double dynamic bonds for silicon anode of lithium-ion batteries. (1st September 2022) - Li, Jiawei; Wang, Yong; Xie, Xin; Kong, Zhao; Tong, Yihong; Xu, Hongyuan; Xu, Hui; Jin, Hong
Abstract: In this work, a novel three-dimensional binder (termed as SPS) based on double dynamic chemical bonds for silicon (Si) anodes has been explored by in-situ crosslinking of starch and polyvinyl alcohol (PVA), where the sodium tetraborate (ST) was used as the crosslinker. This SPS binder introduces a large amount of hydrogen bonds and dynamic borate ester bonds to construct a flexible and robust network to mechanically support the electrode. Besides, it exhibits a self-healing effect which can effectively alleviate the structure damage induced by huge volume variation of the Si anode. Moreover, this unique binder is capable to promote Li + transportation efficiency and improve the cycling stability of the Si anode by maintaining a stable SEI layer. Consequently, under the support of this SPS binder, the Si anode shows an excellent electrochemical performance. The Si@SPS electrode exhibits a high specific capacity of 1011 mAh g −1 after 300 cycles at the current density of 1 A g −1, and retains a relative steady Coulombic efficiency after two cycles.